v.3 - "Ranjan, Ravi" (New Delhi, 2009)
This book has been published into four volumes consisting of Indian constitution, federal polity, fundamental rights, directive principles and diverse aspects of Indian government etc. The book finds its comprehensive treatment about all the above enumerated facts.
Keywords: Government-India